A child with autoimmune polyendocrinopathy candidiasis and ectodermal dysplasia treated with immunosuppression: a case report - O’Gorman, Clodagh S (BioMed Central, 2013)
INTRODUCTION: Common features of autoimmune polyendocrinopathy-candidiasis-ectodermal dysplasia include candidiasis, hypoparathyroidism and hypoadrenalism. The initial manifestation of autoimmune polyendocrinopathy-candidiasis-ectodermal dysplasia may be autoimmune hepatitis, keratoconjunctivitis, frequent fever with or without a rash, chronic diarrhea, or different combinations of these with or without oral candidiasis. CASE PRESENTATION: We discuss a profoundly affected 2.9-year-old Caucasian girl of Western European descent with a dramatic response to immunosuppression (initially azathioprine and oral steroids, and then subsequently mycophenolate mofetil monotherapy). At four years of follow-up, her response to mycophenolate mofetil is excellent. CONCLUSION: The clinical features of autoimmune polyendocrinopathy-candidiasis-ectodermal dysplasia may continue for years before some of the more common components appear. In such cases, it may be life-saving to diagnose autoimmune polyendocrinopathy-candidiasis-ectodermal dysplasia and commence therapy with immunosuppressive agents. The response of our patient to immunosuppression with mycophenolate mofetil has been dramatic. It is possible that other patients with this condition might also benefit from immunosuppression.